Can rodent outbreaks be driven by major climatic events? Evidence from cyclone Nargis in the Ayeyawady Delta, Myanmar - Htwe, Nyo Me; Singleton, Grant R.; Nelson, Andrew D. (Wiley, 2013)
Asynchronous planting following cyclone Nargis provided abundant high‐quality food for an extended period, which in turn led to a lengthened breeding season of rodents. The outbreak of populations 15 months after cyclone Nargis is consistent with the time it would take rodent populations to build from a low base after a major flooding event. To prevent rodent outbreaks effectively, synchronous planting, use of rice varieties with a similar maturation date and good field sanitation are important actions for subsequent rice crops after a major weather event. © 2012 Society of Chemical Industry